LEARNING STRATEGY OF VIRTUAL EXTERNAL CONTEXT LANDSCAPE IN EDUCATIONAL PRAGMATICS (STRATEGI PEMBELAJARAN LANSKAP KONTEKS EKSTERNAL VIRTUAL DALAM PRAGMATIK EDUKASIONAL) - R. Kunjana Rahardi (Universitas PGRI Sumatera Barat, 2021)
AbstractThe purpose of this study is to develop virtual external context landscape learning strategy in the educational pragmatics course so that the improvement of the quality of educational pragmatics learning in the Master program of the Indonesian language education in response to covid-19 pandemic can be done. This research is included in the type of development research with modifications as necessary in accordance with the target achievements of this development research. The steps of research on the development of a virtual external context landscape learning strategy are as follows: (1) data collection and analysis for a preliminary product of development study, (2) product development planning, (3) product draft development, (4) testing early stage field trials, (5) revision of field trial results, (6) second stage field trials, (7) product improvement of field test results, (8) final stage field testing, (9) final product improvement, and (10) ) dissemination and implementation. This research is theoretically useful in terms of developing pragmatic linguistics, especially educational pragmatics, and is practically useful in terms of improving the educational pragmatic learning model in the master program in response to Covid-19 pandemic.Keywords: Learning Model, Context Landscape, Educational PragmaticsAbstrakTujuan penelitian ini adalah untuk mengembangkan strategi pembelajaran lanskap konteks eksternal virtual dalam mata kuliah Pragmatik Edukasional sehingga peningkatan kualitas pembelajaran Pragmatik Edukasional di program magister pendidikan bahasa Indonesia dalam rangka menyikapi pandemi covid-19 dapat dilakukan. Penelitian ini termasuk dalam jenis penelitian pengembangan dengan modifikasi seperlunya sesuai dengan target capaian penelitian pengembangan ini. Langkah-langkah dalam penelitian pengembangan strategi pembelajaran lanskap konteks eksternal virtual tersebut secara lengkap disampaikan sebagai berikut: (1) pengumpulan dan analisis data untuk studi pendahuluan pengembangan produk, (2) perencanaan pengembangan produk, (3) pengembangan draf produk, (4) uji coba lapangan tahap awal, (5) revisi hasil uji coba lapangan, (6) uji coba lapangan tahap kedua, (7) penyempurnaan produk hasil uji lapangan, (8) uji lapangan tahap akhir, (9) penyempurnaan produk akhir, dan (10) diseminasi dan implementasi. Penelitian ini bermanfaat secara teoretis dalam hal pengembangan ilmu bahasa pragmatik khususnya pragmatik edukasional, dan secara praktis bermanfaat dalam kaitan dengan perbaikan model pembelajaran pragmatik edukasional di program magister dalam rangka menyikapi pandemi Covid-19.Kata Kunci: Model Pembelajaran, Lanskap Konteks, Pragmatik Edukasional